2005
DOI: 10.1007/s10342-004-0047-1
|View full text |Cite
|
Sign up to set email alerts
|

Site quality evaluation by classification tree: an application to cork quality in Sardinia

Abstract: Cork harvesting and stopper production represent a major forest industry in Sardinia (Italy). The target of the present investigation was to evaluate the ''classification tree'' as a tool to discover possible relationships between microsite characteristics and cork quality. Seven main cork oak (Quercus suber) producing areas have been identified in Sardinia, for a total of more than 122,000 ha. Sixty-three sample trees, distributed among different geographical locations and microsite conditions, were selected.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
0
14
0
4
Order By: Relevance
“…Empirical experience has shown that cork oak trees which produce good cork quality, tend to maintain this standard in successive strippings throughout their productive life [7]. In the same way, it has been observed that there are productive areas, where trees tend to have greater cork thickness, and that these areas retain their productivity level throughout the cycle.…”
Section: Introductionmentioning
confidence: 60%
See 2 more Smart Citations
“…Empirical experience has shown that cork oak trees which produce good cork quality, tend to maintain this standard in successive strippings throughout their productive life [7]. In the same way, it has been observed that there are productive areas, where trees tend to have greater cork thickness, and that these areas retain their productivity level throughout the cycle.…”
Section: Introductionmentioning
confidence: 60%
“…Cork thickness is related to site conditions, as stated by Ferreira et al [14], Corona et al [7] and Montero and Cañellas [32]. Despite this, the site index proposed by Sánchez-González et al [38] is not significantly correlated with random plot effects.…”
Section: Identification Of Variables Influencing Cork Thicknessmentioning
confidence: 76%
See 1 more Smart Citation
“…8). La loro relativa omogeneità nel livellarsi verso il basso indipendentemente dai differenti contesti stazionali e comportamenti imprenditoriali, può essere in parte ricondotta alla modesta capacità di ritenzione idrica dei suoli superficiali e grossolani della Gallura capaci, d'altra parte, di esaltare la qualità del sughero (Dettori et al 1997, Corona et al 2005. La stretta correlazione tra disponibilità idrica annuale, funzionale a entità e distribuzione delle precipitazioni, e accrescimento radiale della quercia è segnalata da numerosi Autori sia per l'intero fusto (Costa et al 2001e 2002 sia in riferimento al sughero (Caritat et al 1996, Fialho et al 2001.…”
Section: Discussione Dei Risultati E Conclusioniunclassified
“…Poiché l'accrescimento di legno e sughero, e la qualità del secondo, sono legati all'interazione tra fattori genetici e ambientaliselvicolturali (Vieira 1950, Montero & Cañellas 2003, Corona et al 2005, una scelta errata delle provenienze può concorrere all'insuccesso degli imboschimenti, in tempi medi (accrescimenti nella fase giovanile) e lunghi (qualità delle plance). L'elevata domanda di postime quercino scaturita dall'applicazione delle misure comunitarie ha colto impreparate le strutture vivaistiche regionali, sia in termini di quantità che di qualità, con spostamento di materiale di propagazione non solo tra i diversi comprensori sughericoli regionali ma anche sulle lunghe distanze, tanto da doversi registrare l'introduzione di provenienze iberiche.…”
Section: Introduzioneunclassified